2012
DOI: 10.1111/j.1365-2362.2011.02637.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of liver fibrosis and liver reconstitution of DMN‐treated rat liver by transplanted EPCs

Abstract: EPC transplantation effectively promotes the remodelling of tissues damaged by liver fibrosis; it can also reconstitute sinusoids in chronic liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…In addition, IHC of frozen sections confirmed that more blood vessels were formed in the liver after treatment with HD cultured cells [15]. The enhancement of capillary density was coinciding with the treatment by EPCs Prevention of liver fibrosis and liver reconstitution of DMN-treated rat liver by transplanted EPCs [28]. Interestingly, these findings are conflicting with the reports that liver fibrogenesis and angiogenesis develop in parallel during progression towards cirrhosis [29], [30].…”
Section: Discussionmentioning
confidence: 90%
“…In addition, IHC of frozen sections confirmed that more blood vessels were formed in the liver after treatment with HD cultured cells [15]. The enhancement of capillary density was coinciding with the treatment by EPCs Prevention of liver fibrosis and liver reconstitution of DMN-treated rat liver by transplanted EPCs [28]. Interestingly, these findings are conflicting with the reports that liver fibrogenesis and angiogenesis develop in parallel during progression towards cirrhosis [29], [30].…”
Section: Discussionmentioning
confidence: 90%
“…VEGF, SDF‐1 and IGF‐1) that promote the migration of resident progenitor cells and mature endothelial cells to contribute to neovascularization . The important role of EPCs is supported by the finding that their levels are reduced or dysfunctional in some diseases such as diabetes , and also by the functional improvement of tissues after EPC transplantation in different disease models .…”
Section: Adult Stem Cell Migration In Physiological and Pathological mentioning
confidence: 99%
“…The critical role of EPCs is suggested by their dysfunction and reduced levels in clinical disease states associated with poor wound healing, such as diabetes [47,48], and the observation that EPC transplantation can ameliorate injury and improve functional outcomes in models of stroke [13], myocardial infarction [14] and acute liver and lung injury [15,16]. …”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%